Determining whether ethnic minorities with severe obesity face a disproportionate risk of serious disease and death from COVID-19: outcomes from a Southern California-based retrospective cohort study - Qiaowu Li; Hemesh Mahesh Patel; Shefali Khandwala; Poonam Somani; Stephanie Tovar; Alejandra Montano (BMJ Open)
Objective Obesity has been recognised as a risk factor for poor outcomes associated with COVID-19. Ethnic minorities with COVID-19 have been independently found to fare poorly. We aim to determine if ethnic minorities with severe obesity—defined as a body mass index (BMI) above 40 kg/m²—experience higher rates of hospitalisation, invasive ventilation and death.Design and setting Retrospective cohort study from 1 March 2020 to 28 February 2021 within an integrated healthcare organisation in Southern California.Participants We identified 373 831 patients by COVID-19 diagnosis code or positive laboratory test.Methods Multivariable Poisson regression with robust error variance estimated adjusted risks of hospitalisation, invasive ventilator use and death within 30 days. Risks were stratified by ethnicity and BMI.Results We identified multiple differences in risk of poor outcomes across BMI categories within individual ethnic groups. Hospitalisation risk with a BMI over 45 kg/m² was greater in Asian (RR 2.31, 95% CI 1.53 to 3.49; p<0.001), Hispanic (RR 3.22, 95% CI 2.99 to 3.48; p<0.001) and Pacific Islander (RR 3.79, 95% CI 2.49 to 5.75; p<0.001) patients compared with White (RR 2.04, 95% CI 1.79 to 2.33; p<0.001) and Black (RR 2.00, 95% CI 1.70 to 2.34; p<0.001) patients. A similar trend was observed with invasive ventilation risk. The risk of death was greater in Asian (RR 3.96, 95% CI 1.88 to 8.33; p<0.001), Hispanic (RR 3.03, 95% CI 2.53 to 3.61; p<0.001) and Pacific Islander (RR 4.60, 95% CI 1.42 to 14.92; p=0.011) patients compared with White (RR 1.47, 95% CI 1.13 to 1.91; p=0.005) and Black (RR 2.83, 95% CI 1.99 to 4.02; p<0.001) patients with a BMI over 45 kg/m².Conclusions Ethnic minorities with severe obesity, particularly Asian, Hispanic and Pacific Islander patients, had a statistically significant higher risk of hospitalisation, invasive ventilator use and death due to COVID-19. Potential explanations include differences in adipose tissue deposition, overall inflammation and ACE-2 receptor expression.